Kontroversi Hak Asasi Manusia: Studi Penafsiran Mufassir Klasik Dan Kontemporer Mengenai Lgbt - Muhammad Ikhya Ulumuddin; Muhammad Abdullah Faqih (Kuras Institute, 2024)
The concept of human rights (HAM) varies widely among different countries due to differences in government forms, cultures, and religions. Searching for 'al-Haqq' or 'al-Huqūq' in Islamic texts does not capture the essence of HAM, as there is no equivalent term in the Quran. Abd Muin Salim suggests identifying HAM-related verses through the particle lām li al-tamlīk, which indicates ownership. The discussion of HAM often includes the debate over legalizing same-sex marriage, with some Muslim scholars supporting it. These scholars argue that homosexual acts are permissible within a marriage or based on mutual consent. This study uses library research to explore human rights issues concerning LGBT according to classical and contemporary scholars' interpretations. A key error made by supporters of LGBT rights is interpreting the word 'syakilah' as 'fitrah' or 'innate.' No classical or contemporary scholars interpret 'syakilah' to mean 'fitrah' or 'innate.'.